2019
DOI: 10.25159/2520-5293/4439
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Students’ Knowledge, Attitude and Use regarding an Implanted Contraceptive Method

Abstract: Despite the prioritisation of contraceptives in the sustainable development goals for 2030 and their increasing availability, unplanned pregnancy remains a universal problem, representing up to 40 per cent of all reported pregnancies. Many sub-Saharan African countries, including South Africa, have resorted to the use of implanted contraceptives, such as Implanon, to decrease the rate of unintended pregnancies. Therefore, this study sought to assess the knowledge, attitude and use regarding the Implanon contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…14 The result was also much higher than the finding of the study carried out first-and second-year nursing students in South Africa with 58.3% of them had unfavorable attitude. 11 According to current study, majority of participant disagreed that contraceptives such as condom reduced sex drive. This was opposite to a research in Tanzania where nearly two-thirds of participants stated that contraceptive methods decreased sexual desire as well as they recognized that condom could slip off when doing intercourse.…”
Section: Attitude Toward Contraceptive Methodsmentioning
confidence: 70%
See 1 more Smart Citation
“…14 The result was also much higher than the finding of the study carried out first-and second-year nursing students in South Africa with 58.3% of them had unfavorable attitude. 11 According to current study, majority of participant disagreed that contraceptives such as condom reduced sex drive. This was opposite to a research in Tanzania where nearly two-thirds of participants stated that contraceptive methods decreased sexual desire as well as they recognized that condom could slip off when doing intercourse.…”
Section: Attitude Toward Contraceptive Methodsmentioning
confidence: 70%
“…This was similar to the studies in Spain, 10 and South Africa. 11 Most of them were female that perfectly reflected the specific of nursing major. This rate was similar to the study on 178 nursing students in Brazil with 97.75% of female.…”
Section: Discussionmentioning
confidence: 93%
“…For instance, Ukoha and Mooi in a study among Nigerian nursing students revealed that 47.7% of their respondents possessed inadequate knowledge of Implanon. 28 In another study by van Zyl et al, among Health Sciences students in Tanzania, half of the respondents were not aware of subdermal implants and 34.8% have not heard of intrauterine devices. 29 In Nigeria, Aigbiremolen et al, revealed that only 31.2% of undergraduate students had good knowledge of contraceptive methods and their benefits.…”
Section: Discussionmentioning
confidence: 96%